"Maintaining the image of a desired teacher": major issues of late-career senior teacher educators. Issue 5 (3rd September 2021) - Gutman, Mary; Oplatka, Izhar
ABSTRACT: This narrative study explores the late-career issues among 15 senior teacher educators from Israeli Academic Colleges of Education (ACEs), in light of the growing conversation about pre-pension maintenance of senior faculty members employed in teacher education institutions. The data analysis of semi-structured interviews highlighted dedication to daily tasks (research activity, administration, teacher education and leading Professional Learning Communities), and a sense of mission during career experiences (leaving legacy to student teachers and colleagues). It was reflected in two parallel work patterns: the 'work pattern of sharing', and the 'work pattern of expertise'. The discussion raises similarities between the literature and the first work pattern, in line with the unique culture of teacher education systems in the world. However, the existence of the 'work pattern of expertise' in the literature remains vague and requires more in-depth thinking and research.